Three members GP
The sum of three numbers in GP (geometric progression) is 21 and the sum of their squares is 189. Find the numbers.
Thank you for submitting an example text correction or rephasing. We will review the example in a short time and work on the publish it.
Please write to us with your comment on the math problem or ask something. Thank you for helping each other - students, teachers, parents, and problem authors.
Showing 0 comments:
Tips to related online calculators
You need to know the following knowledge to solve this word math problem:
Next similar math problems:
- Tenth member
Calculate the tenth member of geometric sequence when given: a1=1/2 and q=2
- Five members
Write first 5 members geometric sequence and determine whether it is increasing or decreasing: a1 = 3 q = -2
- Geometric sequence 4
It is given geometric sequence a3 = 7 and a12 = 3. Calculate s23 (= sum of the first 23 members of the sequence).
- GP - 8 items
Determine the first eight members of a geometric progression if a9=512, q=2
- Geometric progression 4
- Six terms
Find the first six terms of the sequence a1 = -3, an = 2 * an-1
- Geometric progression 2
There is geometric sequence with a1=5.7 and quotient q=-2.5. Calculate a17.
By introducing a new variable solve biquadratic equation: ?
In the classroom, students always give candy to their classmates on their birthdays. The birthday person always gives each one candy, and he does not give himself. A total of 650 candies were distributed in the class per year. How many students are in the
How much is sum of square root of six and the square root of 225?
- Solve equation
solve equation: ?
- Quadratic equation
Find the roots of the quadratic equation: 3x2-4x + (-4) = 0.
Find variable P: PP plus P x P plus P = 160
Equation ? has one root x1 = 8. Determine the coefficient b and the second root x2.
Determine the quadratic equation absolute coefficient q, that the equation has a real double root and the root x calculate: ?
Determine the discriminant of the equation: ?
- Solve 3
Solve quadratic equation: (6n+1) (4n-1) = 3n2